PROCESS AND IMPORTANCE OF BRAINSTORMING TO SCHOOL CHILDREN DURING CLASS ACTIVITIES - D. X. Safarova (Zeta Repository, 2023)
This study aimed at identifying the impact of brainstorming strategy on improving writing skills of high school pupils. Nowadays, most of the school children are facing with difficulties with brainstorming and gathering ideas while writing an essay. The reasons for this issue may be narrow-mind and lack of reading books. Teachers can help people to improve the brainstorming performance.